2003
DOI: 10.1038/sj.bjc.6601235
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation and cognition in prostate cancer

Abstract: Androgen deprivation (AD) is commonly used in neoadjuvant and adjuvant setting with prostate cancer (PC) radiotherapy. This prospective study assessed whether cognitive functioning is impaired during 12 months of AD therapy. Longitudinal testing of 25 patients treated with AD and curative radiotherapy was undertaken at baseline, and at 6 and 12 months. CogniSpeed r software was used for measuring attentional performances. Other cognitive performances were evaluated using verbal, visuomotor and memory tests. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 33 publications
5
109
1
3
Order By: Relevance
“…The search revealed a total of 11 studies examining ADT in relation to objective cognitive performance. [40][41][42] Our primary focus was effects on specific cognitive domains including verbal memory (e.g., memory for word lists), visual memory (e.g., memory for geometric designs), spatial memory (e.g., route memory), spatial abilities (e.g., mental rotations), attention, verbal fluency, processing speed, executive function (e.g., planning and mental flexibility) and working memory. Additionally, when available, we report findings based on a Reliable Change Index (RCI) calculation or a similar approach.…”
Section: Evidence For Cognitive Effects Of Testosteronementioning
confidence: 99%
See 3 more Smart Citations
“…The search revealed a total of 11 studies examining ADT in relation to objective cognitive performance. [40][41][42] Our primary focus was effects on specific cognitive domains including verbal memory (e.g., memory for word lists), visual memory (e.g., memory for geometric designs), spatial memory (e.g., route memory), spatial abilities (e.g., mental rotations), attention, verbal fluency, processing speed, executive function (e.g., planning and mental flexibility) and working memory. Additionally, when available, we report findings based on a Reliable Change Index (RCI) calculation or a similar approach.…”
Section: Evidence For Cognitive Effects Of Testosteronementioning
confidence: 99%
“…We review three studies with that simple design. [40][41][42] A better study design is one where the patient groups are tested at baseline and after treatment and compared to a control group tested at two sessions spaced at equal intervals. Such a design allows an estimation of change in performance related to ADT given what would be expected in the absence of ADT.…”
Section: Evidence For Cognitive Effects Of Testosteronementioning
confidence: 99%
See 2 more Smart Citations
“…Low testosterone levels may, in fact, alter serotonin neurotransmission [8], negatively affecting mood as demonstrated in animal models [9]. Also, testosterone deficiency may decrease cerebral perfusion in the brain regions involved in memory, reasoning, judgment, and emotions [10], leading to a deterioration in mental and overall wellbeing [11,12]. Studies in elderly subjects and non-cancer patients have reported a clear association between testosterone levels and depressive symptoms [13]: lower testosterone levels in older men have been associated with more depressive symptoms [14,15], which seem to disappear with testosterone hormone treatment [16,17].…”
Section: Introductionmentioning
confidence: 99%